MODERN PROBLEMS OF HUMAN RESOURCE MANAGEMENT - Elena Ponomareva; Malvina Gyulnezerova (Вестник Северо-Кавказского федерального университета)
The article discusses the essence, the emergence reasons, types of the problems of human resource management which have arisen when hiring workers in the organization during the training, compensation, ensuring development, management of a personnel reserve are considered, and also their negative impact on functioning of any enterprise. The main problems of human resource management in modern conditions, on the example of the oil company JSC Lukoil, and a way of their decision, and also strategy and problems of human resource management of the enterprise are analyzed.